AKUNTANSI & PENERAPAN PAJAK PERTAMBAHAN NILAI (PPN) MENGGUNAKAN APLIKASI E-FAKTUR PADA PT DINAMIKA ENERGY INDONESIA - Zhira Farah Azzahra (2023)
This study aims to analyze the Value Added Tax (VAT) reporting procedure using the e-faktur application at PT Dinamika Energy Indonesia. This research is focused on creating tax invoices and reporting Value Added Tax (VAT) using the e-Faktur application. This research is a qualitative research with a descriptive approach. The object of research is VAT expenditure and income at PT Dinamika Energy Indonesia. Data obtained through documentation studies and interviews. The collected research data were analyzed using qualitative data analysis techniques. The results of the study show that reporting VAT using the e-Faktur application makes work easier and more efficient.